Proliferation inhibition and apoptosis induction of imatinib-resistant chronic myeloid leukemia cells via PPP2R5C down-regulation - Shen, Qi (BioMed Central, 2013)
Despite the success of imatinib and other tyrosine kinase inhibitors (TKIs), chronic myeloid leukemia (CML) remains largely incurable, and a number of CML patients die due to Abl mutation-related drug resistance and blast crisis. The aim of this study was to evaluate proliferation inhibition and apoptosis induction by down-regulating PPP2R5C gene expression in the imatinib-sensitive and imatinib-resistant CML cell lines K562, K562R (imatinib resistant without an Abl gene mutation), 32D-Bcr-Abl WT (imatinib-sensitive murine CML cell line with a wild type Abl gene) and 32D-Bcr-Abl T315I (imatinib resistant with a T315I Abl gene mutation) and primary cells from CML patients by RNA interference. PPP2R5C siRNAs numbered 799 and 991 were obtained by chemosynthesis. Non-silencing siRNA scrambled control (SC)-treated, mock-transfected, and untreated cells were used as controls. The PPP2R5C mRNA and protein expression levels in treated CML cells were analyzed by quantitative real-time PCR and Western blotting, and in vitro cell proliferation was assayed with the cell counting kit-8 method. The morphology and percentage of apoptosis were revealed by Hoechst 33258 staining and flow cytometry (FCM). The results demonstrated that both siRNAs had the best silencing results after nucleofection in all four cell lines and primary cells. A reduction in PPP2R5C mRNA and protein levels was observed in the treated cells. The proliferation rate of the PPP2R5C-siRNA-treated CML cell lines was significantly decreased at 72 h, and apoptosis was significantly increased. Significantly higher proliferation inhibition and apoptosis induction were found in K562R cells treated with PPP2R5C-siRNA799 than K562 cells. In conclusion, the suppression of PPP2R5C by RNA interference could inhibit proliferation and effectively induce apoptosis in CML cells that were either imatinib sensitive or resistant. Down-regulating PPP2R5C gene expression might be considered as a new therapeutic target strategy for CML, particularly for imatinib-resistant CML.